Dynamic reconfiguration of web service in service-oriented architecture - Ilahi, Rahmat; Admodisastro, Novia; Mohd Ali, Norhayati; Md Sultan, Abu Bakar (American Scientific Publishers, 2017)
Dynamic reconfiguration of web services is an important role in Service-Oriented Architecture (SOA) that has an ability to adapt changes in Service-based systems during runtime stage without interrupting existing services or business processes. This is crucial to prevent Service-based Systems from failure while the environment is changing or to allow system being modify immediately whenever necessary. However, dynamic reconfiguration in SOA is a difficult process and presently there are lacked of attempts to handle the process appropriately. In this paper, we present a study of related works of dynamic reconfiguration of the web services in SOA. The study is crucial to provide a basis for developing our proposed solution, Dynamic Reconfiguration of Web Service (DREWS). The basic concepts of DREWS are discussed in this paper.